2010
DOI: 10.1002/cbic.201000551
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing in Bacterial Species that Use Degenerate Autoinducers Can Be Tuned by Using Structurally Identical Non‐native Ligands

Abstract: Many bacteria use quorum sensing (QS) to regulate cell-density dependent phenotypes that play critical roles in the maintenance of their associations with eukaryotic hosts. In Gram-negative bacteria, QS is primarily controlled by N-acylated l-homoserine lactone (AHL) signals and their cognate LuxR-type receptors. AHL-LuxR-type receptor binding regulates the expression of target genes necessary for QS phenotypes. We recently identified a series of non-native AHLs capable of intercepting AHL-LuxR binding in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 112 publications
4
57
0
3
Order By: Relevance
“…Interestingly, different AHL receptor proteins can engage in different binding interactions with a given ligand despite the fact that the ligand-binding sites of the various LuxR-type proteins on average share 75% homology (167,171,(198)(199)(200). This has been confirmed by crystal structures demonstrating that a given AHL can occupy slightly different conformations within the ligand-binding sites of different LuxR-type proteins and that conserved binding-site residues can serve distinct functionalities for ligand binding within these different receptors (178).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, different AHL receptor proteins can engage in different binding interactions with a given ligand despite the fact that the ligand-binding sites of the various LuxR-type proteins on average share 75% homology (167,171,(198)(199)(200). This has been confirmed by crystal structures demonstrating that a given AHL can occupy slightly different conformations within the ligand-binding sites of different LuxR-type proteins and that conserved binding-site residues can serve distinct functionalities for ligand binding within these different receptors (178).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 87%
“…5) (198). Other studies from the Blackwell lab have demonstrated the applicability of various compounds against the pathogenic actions of E. carotovora on Solanum tuberosum (potato) and of P. syringae on Phaseolus vulgaris (green bean), and several compounds showed promising results modulating quorum sensing in both bacteria, though the timing and dosage of treatments, especially in the potato model, were critical (199,201). In another example of cross-inhibition, a high-throughput chemical screen of approximately 35,000 compounds led to the identification of 15 small molecules that inhibited the LuxN/AI-1 QS circuit in V. harveyi (129).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Данная система представляет собой способ межклеточных бактериальных коммуникаций, зависящий от плотности клеток на единицу объема, вовлеченный в экспрессию генов (в т.ч. генов вирулентности для экзоэнзимов, эк-зополисахаридов) и связанными с этим изменениями в поведении бактерий, нахо-дящихся в биопленке, включая их сопро-тивляемость к изменяющимся условиям внешней среды при большой плотности бактериальной колонии [39][40][41]. Основные известные на сегодня системы межмикроб-ных взаимодействий описаны как система белковых рецепторов LuxR-LuxI у грамо-трицательных бактерий, которая использу-ет N-ацил-гомосеринлактон в качестве сиг-нальной молекулы и сигнальные системы agr/fsr, использующие РНКIII в качестве эффекторных молекул.…”
Section: нарушение работы механизмов систем межмикробных взаимодействийunclassified
“…Ряд идентифицированных к настоя-щему моменту таких ингибиторов пред-ставляют собой вещества, продуцируемые растениями в качестве неспецифического средства защиты против бактериальной ко-лонизации, хотя есть и искусственно син-тезированные вещества [41,43], и даже выделенные непосредственно из числа про-дуцируемых самими бактериями -в част-ности, фенэтиламид и циклический дипеп-тид [44]. Ho KK et al [43] в своей работе показали, что 5-метилен-1-(проп-2-эноил)-4-фенил-дигидропиррол-2-1 способен предотвращать формирование биопленки Pseudomonas aeruginosa и Staphylococcus aureus при его использовании в качестве компонента искусственного защитного по-крытия в модельном эксперименте.…”
Section: нарушение работы механизмов систем межмикробных взаимодействийunclassified
“…The quorum-quenching bacteria identified so far belong to the Delftia, Ochrobactrum, Bacillus, and Rhodococcus genera. The colonization of potato plant roots by the quorum-quenching Rhodococcus was shown to be enhanced using the growth-stimulating agents gamma-caprolactone and gamma-heptalactone (55)(56)(57)(58)(59)(60)(61).…”
mentioning
confidence: 99%